The evolution of international definitions of fatty liver disease and insights into the working definition and features of the 2024 Chinese guideline - Li CHEN; Jiangao FAN (Zhongguo Linchuang Yixue)
Since 2020, the international community has successively proposed new nomenclatures for metabolic dysfunction-associated fatty liver disease (MAFLD) and metabolic dysfunction-associated steatotic liver disease (MASLD). In 2024, the Chinese Society of Hepatology updated and published the Guideline for the prevention and treatment of metabolic dysfunction-associated (non-alcoholic) fatty liver disease (version 2024). This review deeply analyzes the differences between MASLD and MAFLD in terms of concept, definition framework, and clinical management. On this basis, it provides an in-depth interpretation of the updated highlights and features of the working definition in the 2024 updated Chinese guideline.